2021
DOI: 10.3390/su13041817
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rice Husk Biochar Rate on Arbuscular Mycorrhizal Fungi and Growth of Soursop (Annona muricata L.) Seedlings

Abstract: Soursop (Annona muricata L.) is increasingly planted in Malaysia for its agronomical importance as a multipurpose plant with medicinal and health benefits. However, there is limited information on soursop cultivation in Malaysia. Soursop can be inoculated with arbuscular mycorrhizal fungi (AMF) as a sustainable approach for successful seedlings growth before transplanting to field. As a beneficial symbiotic soil microorganism, AMF has been known as biofertilizer which can improve soil conditions and plant grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Our results were similar with a previous study which found that the combination of biochar and AMF increased plant growth ( Hashem et al, 2019 ). Combination of biochar and AMF increased shoot and root biomass, leaf area meter, root surface area and root length in soursop ( Annona muricata L.) seedlings ( Harun et al 2021 ). Similar results were reported by Budi and Setyaningsih (2013) .…”
Section: Discussionmentioning
confidence: 99%
“…Our results were similar with a previous study which found that the combination of biochar and AMF increased plant growth ( Hashem et al, 2019 ). Combination of biochar and AMF increased shoot and root biomass, leaf area meter, root surface area and root length in soursop ( Annona muricata L.) seedlings ( Harun et al 2021 ). Similar results were reported by Budi and Setyaningsih (2013) .…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that the pore properties of rice husk biochar will be more developed at higher pyrolysis temperatures because of the greater formation of turbostratic crystallites [27]. Regarding the applications of rice husk biochar, it has been used as an effective adsorbent for the removal of trichloroethylene [28], a good medium for the growth of soursop (Annona muricata L.) seedlings [29] and a soil amendment for increasing nutrient retention [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Budi and Setyaningsih (2013) reported that AMF and biochar promote shoot dry weight in Melia azedarach Linn. Harun et al (2021) informed that combined with AMF and biochar improved "shoot and root biomass" and root length in Annona muricata L. Dual applications of AMF and biochar enhance N, C, and chlorophyll content in drought conditions. Similarly, Li and Cai (2021) investigated dual biochar, and AMF improved the P content of maize in water stress.…”
Section: Discussionmentioning
confidence: 98%